2022
DOI: 10.3389/fnut.2022.968073
|View full text |Cite
|
Sign up to set email alerts
|

The association of healthy eating index with periodontitis in NHANES 2013–2014

Abstract: BackgroundPeriodontal disease is very common worldwide and is one of the main causes of tooth loss in adults. Periodontal disease is characterized by chronic inflammation that can destroy adjacent alveolar bone and lead to a loss of periodontal ligaments. Although previous studies have found that a daily diet can influence the development of periodontal disease (e.g., a diet low in carbohydrates and rich in vitamins C and D and fiber can have a protective effect). Periodontal disease may present as gingivitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…The biological mechanism of the relationship between periodontitis and kidney damage is unclear, which may be related to bacteria, host genetic characteristics, oxidative stress and inflammatory response. 34,41 The following two possible mechanisms are in focus: (1) local inflammation in periodontal tissue causes low-grade systemic inflammatory response, which promotes systemic diseases such as CKD and AS 42,43 and (2) periodontal bacteria or their virulence factors enter systemic circulation through damaged periodontal tissue and reach kidney tissue. 10,44 The final result of these two pathways is that the immune inflammatory system of the kidney is activated, then inflammatory cells gather in the kidney, various inflammatory cytokines are released, and finally the renal inflammatory response is aggravated, resulting in tissue homeostasis and cellular function damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological mechanism of the relationship between periodontitis and kidney damage is unclear, which may be related to bacteria, host genetic characteristics, oxidative stress and inflammatory response. 34,41 The following two possible mechanisms are in focus: (1) local inflammation in periodontal tissue causes low-grade systemic inflammatory response, which promotes systemic diseases such as CKD and AS 42,43 and (2) periodontal bacteria or their virulence factors enter systemic circulation through damaged periodontal tissue and reach kidney tissue. 10,44 The final result of these two pathways is that the immune inflammatory system of the kidney is activated, then inflammatory cells gather in the kidney, various inflammatory cytokines are released, and finally the renal inflammatory response is aggravated, resulting in tissue homeostasis and cellular function damage.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis (PA) is an immune inflammatory disease that occurs in periodontal tissue caused by periodontal plaque microorganisms, its continuous development and aggravation can cause periodontal tissue destruction and loss, which in turn leads to tooth loosening and shedding. 1,2 In addition to the local damage in the oral cavity, which affects the oral masticatory function and facial aesthetics, more and more studies in recent years have shown that periodontitis is also associated with systemic diseases such as diabetes, hypertension, cardiovascular disease and chronic kidney disease (CKD). 3 A number of recent studies have shown a strong association between periodontitis and CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic data (age, education, race, and PIR) were obtained through a household interview survey. PIR was categorized into three groups: low (< 1.35), medium (1.35 to < 3.0), and high (≥ 3.0) [ 14 ]. BMI information was measured in the mobile examination center, and recoded into four categories: underweight (< 18.5 kg/m 2 ); normal weight (18.5 to ≤ 24.9 kg/m 2 ); overweight (25 to ≤ 29.9 kg/m 2 ); obese (> 30 kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Four moderation components (sodium, refined grains, added sugars, and saturated fats) are 0–10 points each. The components’ points were summed to compute the final HEI-2015 score [ 21 ]. It should be noted that the calculation was not based on the absolute amount of components but on the energy density per 1000 kcal, which can be extracted from FPED.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the calculation was not based on the absolute amount of components but on the energy density per 1000 kcal, which can be extracted from FPED. In our study, following previous studies, dietary information was extracted from the Total Nutrient Intakes of the First Day (DR1TOT_I) in NHANES and further transformed and calculated with the help of data from FPED [ 12 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%